2002
DOI: 10.1128/jb.184.1.126-133.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cis- and trans- Acting Factors Involved in Regulation of the Streptococcus mutans Fructanase Gene ( fruA )

Abstract: There are two primary levels of control of the expression of the fructanase gene (fruA) of Streptococcus mutans: induction by levan, inulin, or sucrose and repression in the presence of glucose and other readily metabolized sugars. The goals of this study were to assess the functionality of putative cis-acting regulatory elements and to begin to identify the trans-acting factors involved in induction and catabolite repression of fruA. The fruA promoter and its derivatives generated by deletions and/or site-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 43 publications
8
62
0
Order By: Relevance
“…4), although AgD activity was slightly higher in the ccpA and ccpB strains following growth in either glucose or galactose, supplemented with agmatine. This observation is consistent with studies of other metabolic pathways in S. mutans that showed that even though cre sequences were tightly linked to the regulatory regions, CcpA (RegM) and CcpB are not primary factors controlling CCR in this organism (40).…”
Section: Vol 188 2006supporting
confidence: 80%
See 1 more Smart Citation
“…4), although AgD activity was slightly higher in the ccpA and ccpB strains following growth in either glucose or galactose, supplemented with agmatine. This observation is consistent with studies of other metabolic pathways in S. mutans that showed that even though cre sequences were tightly linked to the regulatory regions, CcpA (RegM) and CcpB are not primary factors controlling CCR in this organism (40).…”
Section: Vol 188 2006supporting
confidence: 80%
“…AgD activity was measured in S. mutans UA159 and in otherwise isogenic mutants of this strain lacking the ccpA or ccpB genes that were constructed previously in our laboratory (40). The strains were grown in TV broth containing 25 mM glucose or the nonrepressing sugar, galactose, with or without 10 mM agmatine, to mid-exponential phase prior to measurement of enzyme activity.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…CRE-S resides in close proximity to the Ϫ35 sequence, and CRE-W overlaps partly with the ArcR binding site; therefore, sequence alterations in either CRE could profoundly affect the transcriptional activity of the arc operon. A similar challenge was noted previously in our laboratory, with transcriptional analysis of two putative CREs in the promoter region of the fruA gene of S. mutans, when mutation of a CRE that overlapped with the extended Ϫ10 promoter greatly reduced fruA promoter activity (30). Notably, differences between changes in ADS expression in response to CCR in these two mutants were small and possibly not biologically significant, at least under the conditions tested.…”
Section: Vol 188 2006 Induction and Repression Of Arc Genes 945mentioning
confidence: 70%
“…In S. xylosus, deletion of the cre located in front of the malRA operon (for maltose/maltotriose utilization) causes a complete relief from CCR for ␣-glucosidase (204). Similarly, deletion of a cre located right behind the transcription initiation site of the fructan hydrolase-encoding fruA gene of Streptococcus mutans causes a relief from glucose repression (93,946). CCR of the ␤-amylase-encoding bamM gene from B. megaterium is mediated by a cre located in the DNA region encoding the signal peptide of this extracellular enzyme (457).…”
Section: The Catabolite Response Element Cre Anmentioning
confidence: 99%